Pengaruh Struktur Aktiva, Ukuran Perusahaan, Profitabilitas Dan Tingkat Pertumbuhan Terhadap Struktur Modal - Kepakisan, I Dewa Agung Kresna (E-Jurnal Manajemen; Vol 4 No 1 (2015), 2015)
Asset structure is a permanent payment that contains private asset and foreign asset. The using of foreign asset will cause fixed loads. A company if in the process to fulfill its funding needs prioritize compliance by inside source of company would decrease its dependence to outsider. Food and drink company is a company that active in food and drink industry. But it’s still possible that this company is needed by people so its prospect is favorable now and in the future. The purpose of this research is to know significantly effect of active structure, company standard, profitability, and growth level simultaneously and partially to asset structure in food and drink industry that registered in Bursa Efek Indonesia period 2008-2012. From the test result known simultaneously that active structure, company standard, profitability, and growth level don’t affect significantly to asset structure meanwhile partially active structure variable and company structure have significant effect to asset structure in food and drink industry.
Keywords: active structure; company standard; profitability; growth leve; asset structure.